Load countervail access for spectrum management in wireless sensor networks following Industry 4.0 - Uddin, Md Kabir; Khan, M Kamrul Alam; Sobhan, MA; Ahmed, Farruk; Nabi, MN (Bangladesh Journal of Scientific and Industrial Research, 2023)
Attention to the utmost spectrum administration is to ease interference between different operators and to eliminate potential blockings possibility and occupy time slots for the spectrum users of wireless sensor networks. To stop the difficulties, the load countervail access (LCA) algorithm is a given idea that can simply resolve the reciprocal intervention. The effective and efficient practice of the attained frequency spectrum to be smooth and equal dispensation in a reallocation manner, given their specific QoS basics, is agile by the application (LCA). It lets us find the initially licensed spectrum which is unused and released as soon as required. The authors’ aim following the paper, is the total allocation of the estimated resources of the curse wireless spectrum among more intrusive operators that function in a similar comfortable zone of environment coverage to create equality with the given application (LCA) from the water-filling model. Bangladesh J. Sci. Ind. Res. 58(3), 173-178, 2023